The outsider - King, Stephen, 1947-; Patton, Will (New York, NY : Simon & Schuster Audio, 2018)
When a young boy's body is found in the town park, Detective Ralph Anderson finds the evidence and the witnesses all pointing to one of the city's most popular citizens.
Read by Will Patton.
Keywords: Horror fiction; Suspense fiction; Audiobooks